PENGARUH PERTAMBAHAN BERAT BADAN IBU SELAMA HAMIL DENGAN BERAT BADAN LAHIR BAYI - Asri Noviyanti (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
Maternal nutritional status before and during pregnancy affects the growth baby. When the normal maternal nutritional status is likely to have a healthy baby, aterm with normal weight. According Riskesdas (2010) percentage of weight infants born in North Sumatra of 8.2% by weight <2500gr, while 80.4% by weight 2500-4000 g and 11.3% of infants weighing> 4000 g. This research to identify the relationship of maternal weight gain during pregnancy with birth weight. The study used a correlational analytic design. Study sample were 63 respondents. Sampling technique using total sampling. The study was conducted at the Maternity Clinic Sumiariani Sub District of Medan Johor. Data analysis used Chi Square with significance level (?) of 0.05. Results of statistical tests is based on the analysis of values obtained P = 0.00 means that there is a significant relationship between maternal weight gain during pregnancy to birth weight. And OR = 27 means mothers with appropriate weight gain during pregnancy have 27 times the chance of having a baby with normal weight compared with mothers who had weight gain during pregnancy is not appropriate. Conclusion: From these results it can be proven that the mother's weight gain during pregnancy affects the baby weight that will be born. So that every pregnant woman should know about good nutrition during pregnancy. Suggestion: Expected to be used as input for health agencies in an effort to address issues in public health nutrition problems, especially pregnant women so as to reduce the incidence of low birth weight in the community